Tolerance to a new free amino acid-based formula in children with IgE or non-IgE-mediated cow's milk allergy: a randomized controlled clinical trial - Berni Canani Roberto; Nocerino Rita; Leone Ludovica; Di Costanzo Margherita; Terrin Gianluca; Passariello Annalisa; Cosenza Linda; Troncone Riccardo (BMC, 2013)
Abstract Background Amino acid-based formulas (Aaf) are increasingly used in children with cow's milk allergy (CMA). To be labeled hypoallergenic these formulas must demonstrate in clinical studies that they don't provoke reactions in 90% of subjects with confirmed CMA with 95% confidence when given in prospective randomized, double-blind, placebo-controlled challenge (DBPCFC) trials. The majority of available safety data on Aaf derived from patients with IgE-mediated CMA. Considering substantial differences in the immunologic mechanism and clinical presentation of non-IgE-mediated CMA it's important to investigate the hypoallergenicity of these formulas also in these patients. We prospectively assessed the tolerance to a new commercially available Aaf in children affected by IgE- or non-IgE-mediated CMA. Methods Consecutive patients affected by IgE- or non-IgE-mediated CMA, aged ≤ 4 years, were enrolled. DBPCFC was carried out with increasing doses of the new Aaf (Sineall, Humana, Milan, Italy), using validated Aaf as placebo. Faecal concentrations of calprotectin (FC) and eosinophilic cationic protein (ECP) were monitored. Results Sixty patients (44 male, 73.3%, median age 37, 95%CI 34.5-39.6 months, IgE-mediated CMA 29, 48.3%) were enrolled. At the diagnosis clinical symptoms were gastrointestinal (46.6%), cutaneous (36.6%), respiratory (23.3%), and systemic (10.0%). After DBPCFC with the new Aaf, no patient presented early or delayed clinical reactions. Faecal concentration of calprotectin and of ECP remained stable after the exposure to the new Aaf. Conclusions The new Aaf is well tolerated in children with IgE- or non-IgE-mediated CMA, and it could be used as a safe dietotherapy regimen for children with this condition. Trial registration The trial was registered in the ClinicalTrials.gov Protocol Registration System (ID number: NCT01622426).